Certificate of Participation: 5TH International Conference on Creative Multimedia 2025 (ICCM2025) in conjunction with the Digital Futures International Congress 2025 (DIFCON2025) at Multimedia University, Malaysia. - Joelle, Majanil; Salmiah, Abdul Hamid; Azwan, Abidin (Multimedia University, 2025)
Certificate of Participation / presentation of a paper entitled Conceptualizing the Challenges of No-Code Tool Usage in Remote Design Practices